2022
DOI: 10.1002/cbf.3738
|View full text |Cite
|
Sign up to set email alerts
|

Metformin encapsulated gold nanoparticles (MTF‐GNPs): A promising antiglycation agent

Abstract: The generation of advanced glycation end products (AGEs) through nonenzymatic protein glycation contributes to the pathogenesis of long‐lived diabetic problems. Metformin (MTF) is the very first drug having antihyperglycemic effects on type II diabetes mellitus which also possess interaction with dicarbonyl compounds and blocks the formation of AGEs. In the current study, MTF is bioconjugated with glycation‐derived synthesized gold nanoparticles (GNPs) of significant size. Additionally, using various biophysic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…23 Moreover, the present results showed that administration of metformin and gold nanoparticles significantly improved dyslipidemia produced by HFD in agreement C C C with MTF-GNPs (glycation-derived synthesized gold nanoparticles). 24 Similarly, Husam M. Edrees et al 20 who investigated that AuNPs improved blood glucose level, liver enzymes and pro-inflammatory cytokines causing control of hyperglycemia by administration of gold nanoparticles (10 nm size) through an intraperitoneal injection of 2.5 mg/kg b.w./day for 7 day for 30 albino rats…”
Section: Discussionmentioning
confidence: 99%
“…23 Moreover, the present results showed that administration of metformin and gold nanoparticles significantly improved dyslipidemia produced by HFD in agreement C C C with MTF-GNPs (glycation-derived synthesized gold nanoparticles). 24 Similarly, Husam M. Edrees et al 20 who investigated that AuNPs improved blood glucose level, liver enzymes and pro-inflammatory cytokines causing control of hyperglycemia by administration of gold nanoparticles (10 nm size) through an intraperitoneal injection of 2.5 mg/kg b.w./day for 7 day for 30 albino rats…”
Section: Discussionmentioning
confidence: 99%
“…Considering other studies, researchers addressed the natural compound “C‐Phycocyanin” as an effective pigment protein in T2DM 383 . Gold nanoparticles encapsulated with metformin are also evidenced as prompt antiglycation agents 384 …”
Section: Therapeutic Challenges and Current Remedies To Treat Diabete...mentioning
confidence: 99%
“…383 Gold nanoparticles encapsulated with metformin are also evidenced as prompt antiglycation agents. 384 Many diabetic drugs effectively reduce brain inflammation and retard the process of plaque formation. In the treatment of AD, aducanumab, rivastigmine, memantine, donepezil, galantamine, and donepezil combined memantine are the drugs approved by the Food and Drug Administration of the United States.…”
Section: Diabetes and Neurodegenerative Diseasesmentioning
confidence: 99%
“…4,5 The engineered nanoparticle has been used tremendously as a nanomedicine, overcoming several limitations of conventional therapies, including poor water solubility, nonspecific bio-distribution, or limited bioavailability. [6][7][8] The new method for cancer treatment via nanotechnology has been investigated for the past few years. The investigation will proceed in the future by examining the positive effect of nanomedicine on killing the cancer cells.…”
Section: Introductionmentioning
confidence: 99%